A Multisite Trial Comparing Two Cytomegalovirus (CMV) pp65 Antigenemia Test Kits, Biotest CMV Brite and Bartels/Argene CMV Antigenemia - St. George, Kirsten (American Society for Microbiology, 2000)
A total of 513 blood specimens, predominantly from organ transplant recipients, human immunodeficiency virus-positive patients, and bone marrow transplant recipients, were tested for cytomegalovirus (CMV) by culture and pp65 antigenemia across four test sites. Peripheral blood leukocytes were examined by using both the Biotest CMV Brite and the Bartels/Argene CMV Antigenemia kits. A total of 109 specimens were positive for CMV, 106 (97%) were positive by antigenemia, and 34 (31%) were positive by culture. According to the manufacturers' instructions, 150,000 cells were applied per slide for the Biotest kit and 200,000 cells per slide for the Bartels kit. A total of 93 specimens (88%) were positive by the Biotest kit, and 86 (81%) were positive by the Bartels kit. In specimens found to be positive by only one kit, the positive cell counts were low (median, 1; range, 1 to 7). When the data from all four sites were combined and analyzed, there was no statistical difference between the performance of the two kits; the Biotest and Bartels kits were found to be equivalent in sensitivity, specificity, and positive and negative predictive values for the detection of CMV pp65 antigenemia.